(untitled) (Revista Brasileira Multidisciplinar, 2015)
This text is a simple tribute to the workers and especially to the female workers of Lupo factory,current LUPO S/A. It is an attempt to rescue the history of the company, through the memory of the social group who worked and lived at a crucial time for the company: the period extending from 1921 when the company was founded by Henrique Lupo until the late 1980’s when major technological changes have started to occur. As a woman and a former employee of the company, I also draw my memories and combine them with memories of other warrior women to recompose a story that actually are stories. Stories of work, of struggles for survival, of concrete experiences which give meaning to existence. Dreamed stories which often came true, that insist on returning to memory, to revive the past. And these workers, while remember, once again work.